The Neoclassical Theorem and Distribution of Income and Wealth - Sato, K. (Review of Economic Studies, 1966)
Journal Article The Neoclassical Theorem and Distribution of Income and Wealth Get access K. Sato K. Sato United Nations, New York Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 33, Issue 4, October 1966, Pages 331–335, https://doi.org/10.2307/2974430 Published: 01 October 1966